Transcriptomics and proteomics in human African trypanosomiasis: Current status and perspectives - (:unkn) unknown (My University, 2011)
Human African trypanosomiasis, or sleeping sickness, is a neglected vector-borne parasitic disease caused by protozoa of the species Trypanosoma brucei sensu lato. Within this complex species, T. b. gambiense is responsible for the chronic form of sleeping sickness in Western and Central Africa, whereas T. b. rhodesiense causes the acute form of the disease in East Africa. Presently, 1.5 million disability-adjusted life years (DALYs) per year are lost due to sleeping sickness. In addition, on the basis of the mortality, the disease is ranked ninth out of 25 human infectious and parasitic diseases in Africa. Diagnosis is complex and needs the intervention of a specialized skilled staff; treatment is difficult and expensive and has potentially life-threatening side effects. The use of transcriptomic and proteomic technologies, currently in rapid development and increasing in sensitivity and discriminating power, is already generating a large panel of promising results. The objective of these technologies is to significantly increase our knowledge of the molecular mechanisms governing the parasite establishment in its vector, the development cycle of the parasite during the parasite's intra-vector life, its interactions with the fly and the other microbial inhabitants of the gut, and finally human host-trypanosome interactions. Such fundamental investigations are expected to provide opportunities to identify key molecular events that would constitute accurate targets for further development of tools dedicated to field work for early, sensitive, and stage-discriminant diagnosis, epidemiology, new chemotherapy, and potentially vaccine development, all of which will contribute to fighting the disease. The present review highlights the contributions of the transcriptomic and proteomic analyses developed thus far in order to identify potential targets (genes or proteins) and biological pathways that may constitute a critical step in the identification of new t
Keywords: African Research